Assessment of Veterinary Inspection Practices on Quality of Beef Produced In Ibarapa Central Local Government Area of Oyo State, Nigeria - Oyeleke, Oyediran Wasiu (International Journal of Veterinary Sciences Research, 2015)
Beef is an important animal protein source in Nigerian diet and its quality depends on intrinsic and extrinsic attributes. Hence, this study was carried out to assess veterinary inspection practices on quality of beef produced in Ibarapa Central Local Government Area of Oyo State, Nigeria. The findings of this study showed that the butchers were young with mean age of 40.51years and 95.70% were males. All the respondents strongly agreed that facilities such as lighting, carcass carriers, security fence and cooling facilities had never been provided in the study area. The result also showed that 45.70% of the respondents always cleaned the abattoir’s environment once in a week or at month end, and dungs and wastes were dumped around the abattoir. None of the respondents neither hang the beef in the open air nor put it in a deep freezer but always displayed the beef on the table for customers to see. However, all the respondents allowed customers to touch the beef. It was revealed that ante-mortem inspection was always carried out by the Veterinary Officers attached to the abattoirs. The prominent challenges to quality of beef produced are lack of essential infrastructure, training and workshop for the butchers on hygiene practices and use of modern processing equipment. It can be concluded that beef production is a lucrative venture in the study area but the hygiene practices is below Codex Alimentarius recommended standard. It is hereby recommended that the veterinary officers should intensify effort on ante-mortem and post-mortem inspections while health extension workers and other stakeholders should organize a training/workshop on hygiene practices that will improve the quality of beef produced in the study area.